The Enunciation and the image: Benveniste's point of view - Manetti, Giovanni (E|C, 2020)
Is it possible to find the phenomenon of "enunciation" in visual systems as it is found in verbal ones? When we talk about “enunciation” with regard to images, do we use the term literally or metaphorically? Can a distinction be made between “utterance in the strict sense” and “semiotic production”? What are the conditions for having "enunciation in the strict sense"? The following pages try to answer these and other questions, through a path that has a dual purpose: on the one hand, to reconstruct the contexts and ways in which the word "enunciation" in the 1960s and 1970s has gone from a generic use to a technical use and has become a term in the metalanguage of Semiotics; on the other hand, to show how at its origins an attempt was made to verify whether the notion of enunciation, created to describe a phenomenon pertaining to verbal language, was applicable to semiotic systems other than this one - and with what results.